Determination of antibacterial and antioxidant activity of Spondias mombin stem bark extracts - Saiyara, Fabiha; Hussain, Humyra Binte (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology, 2024.